Human Rights in Cyber Space - Bhatnagar, Shivi (Integrated Journal for Research in Arts and Humanities, 2024)
Cyberspace the space of modern world which anyone can join and is the best platform in today's world to express their own views without any hesitation and hussle. But are we truly free in cyberspace that's the big question in today's world. We as human beings have certain rights which our constitution has given from article 14 of the constitution of India, but the rights in cyberspace are not only for any specific country but for world at large and should be unified. This paper tells about and highlights the same human rights in cyberspace and how it should be exercised.